Ignatzschineria larvae Bacteremia in a Myiatic Wound Infection: A Case Report - Nicholas Mielke; FNU Monika; Stephen J. Cavalieri; Manasa Velagapudi (Annals of Internal Medicine: Clinical Cases)
This case report describes the fifth confirmed instance to the author's knowledge of Ignatzschineria larvae bacteremia in the United States. A 77-year-old man from western Iowa with chronic lower extremity edema and ulcers presented with acute leg pain, systemic symptoms, and maggot-infested wounds. Laboratory tests and imaging indicated severe infection, with blood cultures positive for gram-negative rods. Identification of I larvae was confirmed through 16S ribosomal gene sequencing. The patient received intravenous antibiotics, had below-the-knee amputation, and was discharged on a regimen of oral trimethoprim/sulfamethoxazole. This case highlights the rarity of I larvae bacteremia in nontropical regions and the need for further research.